Enhancing Kindergarten Teachers' Capacity: IT-Based Screening for Maladaptive Behavior During COVID-19 - Widyastuti Widyastuti; Ghozali Rusyid Affandi; Akbar Wiguna; Nurfi Laili (Indonesian Journal of Cultural and Community Development, 2023)
In the context of the COVID-19 pandemic, the surge in maladaptive behavior among kindergarten students presents a pressing educational concern. Swift identification of such behaviors is crucial for effective intervention. This quantitative experimental study investigates the efficacy of the "Utilization of Information Technology-based Maladaptive Behavior Screening" training in bolstering the competence of teachers. Through quasi-experimental methods, 49 teachers from 'Aisyiyah Bustanul Athfal in Sidoarjo Regency participated in the training. The assessment tool employed was a comprehension test. Statistical analysis via paired samples t-test revealed a significant enhancement (p = 0.009; p < 0.05) between pre- and post-training performance. The intervention showcased substantial effectiveness (rs = 0.053; rs > 0.5) in elevating the teaching quality at 'Aisyiyah Bustanul Athfal. This study underscores the importance of IT-based tools in addressing maladaptive behavior issues and fortifying teacher aptitude amidst challenging circumstances, with implications extending to diverse educational settings. Highlight: Educational Imperative: The study addresses the heightened maladaptive behavior in kindergarten students during the COVID-19 pandemic, emphasizing the urgency of timely identification for effective intervention. IT-Based Training Impact: The research examines the positive impact of "Utilization of Information Technology-based Maladaptive Behavior Screening" training on teacher competence, demonstrated through significant performance enhancement. Broader Significance: The study reveals the broader applicability of IT-based tools in ameliorating maladaptive behavior issues and enhancing teaching quality, with implications extending to diverse educational settings. Keyword: Maladaptive Behavior, Kindergarten, COVID-19, Information Technology, Teacher Training